EXTREMISM IN PRE-ISLAMIC ARAB SOCIETY: A Perspective on Moderate Values and Tolerance - Sabiruddin, Sabiruddin; Nurfadhilah, Nurfadhilah; Bukhari, Bukhari; Aryanti, Yosi; Engkizar, Engkizar (State Islamic University North Sumatra, 2024)
Abstract: This study is inspired by the social norms of pre-Islamic Arab society, which often sparked issues related to gender equality and tolerance. These norms were marked by acts of inhumane violence that stood in stark contrast to the teachings of Islam. Unfortunately, similar problems still exist in modern society. This article aims to examine the extremism found in the inhumane social rules of pre-Islamic Arab society through the lens of Islamic values of moderation and tolerance, while also reflecting on parallels in today’s world. Using a case study approach and a comparative analysis, the research explores the social conditions of pre-Islamic Arab society alongside current social realities. The study uncovers four key findings. First, the oppression of women through practices like slavery and female infanticide represents acts of severe extremism. Second, the culture of constant warfare, fueled by disputes and tribal fanaticism, was a hallmark of the time. Third, the unfair practices surrounding marriage and divorce caused significant harm to women. Finally, the study highlights striking similarities between the pre-Islamic era and contemporary society, where a lack of commitment to the Islamic principles of moderation and tolerance continues to contribute to social challenges.Keywords: Extremism, social rules, pre-Islamic Arabia, moderate value, and tolerance